EVIDENCE BASED CASE REPORT (EBCR): PENGARUH THERAPY MUSIC TERHADAP KECEMASAN DAN NYERI SELAMA PERSALINAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Childbirth is a natural process that will be experienced by every pregnant woman. In this process there is stretching and widening of the mouth of the uterus as a sign of uterine contractions to push the baby out. Most mothers start to feel intense pain as the uterus contracts. The way to deal with labor pain is by pharmacological and non-pharmacological ways. One way of non-pharmacological management to reduce labor pain and anxiety is by means of music therapy. Purpose: The EBCR aims to determine the effect of music therapy on the intensity of pain and anxiety in the first stage of labour. Method: used in writing EBCR is by searching for evidence through databases from Pubmed and Google Scholar with the year of publication 2017-2022. Result: Giving music therapy intervention proved effective because the mother felt more relaxed and comfortable and felt less pain after being given music therapy. Conclusion: music therapy is an effective way to reduce pain in the first stage of labor.